2017
DOI: 10.1038/bjc.2016.456
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomised controlled trial of erlotinib vs gefitinib in advanced non-small cell lung cancer with EGFR mutations

Abstract: Background:A phase III trial was conducted to compare the safety and efficacy of erlotinib with that of gefitinib in advanced non-small cell lung cancer harbouring epidermal growth factor receptor mutations in exon 19 or 21.Methods:Eligible patients were randomised to receive erlotinib (150 mg per day) or gefitinib (250 mg per day) orally until disease progression or unacceptable toxicity. We aimed to determine whether erlotinib is superior to gefitinib in efficacy. The primary end point was progression-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(156 citation statements)
references
References 26 publications
10
140
2
4
Order By: Relevance
“…Its side effects are modest and most patients tolerate it well . Erlotinib is another EGFR TKI proven to be effective against EGFR‐mutant NSCLC in randomized controlled trials, with adverse effects similar to gefitinib . The concentration and penetration rate of erlotinib in cerebrospinal fluid are significantly higher than that of gefitinib .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its side effects are modest and most patients tolerate it well . Erlotinib is another EGFR TKI proven to be effective against EGFR‐mutant NSCLC in randomized controlled trials, with adverse effects similar to gefitinib . The concentration and penetration rate of erlotinib in cerebrospinal fluid are significantly higher than that of gefitinib .…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled trials comparing EGFR TKIs were published recently. CTONG 0901, comparing first‐line erlotinib to gefitinib in advanced EGFR 19 or 21‐mutated NSCLC, found similar PFS, response rates and overall survival (OS) . The toxicity profiles were also very similar between erlotinib‐treated or gefitinib‐treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…There have been two studies conducted in Asian patients which directly compared erlotinib and gefitinib, but were based on previously treated patients [Yang et al 2015c;Urata et al 2016]. Neither of these studies showed differences in PFS and OS between TKIs.…”
Section: Is There Evidence Of Different Efficacy Between Egfr Tkis Fomentioning
confidence: 99%
“…ARCHER-1050, NCT01774721, is another ongoing study compar-ing first vs second-generation EGFR-TKI (gefitinib vs dacomitinib), but results are not available yet. CTONG 0901 is a phase II study of erlotinib vs gefitinib which didn't show any significant survival differences between the two treatment arms (Yang et al, 2015b). Finally the impressive efficacy results observed with the thirdgeneration EGFR-TKI osimertinib in the first-line cohort of AURA study (RR: 77%, PFS: 19.7 months) (Ramalingam et al, 2016) have led to the design of the randomized phase III FLAURA trial.…”
Section: Direct Comparisonsmentioning
confidence: 99%